A Database of Underwater Radiated Noise from Small Vessels in the Coastal Area - Mark Shipton; Juraj Obradović; Fausto Ferreira; Nikola Mišković; Tomislav Bulat; Neven Cukrov; Roee Diamant (Scientific Data)
Abstract The current procedures for measuring underwater radiated noise (URN) are designed for cooperating vessels in controlled areas. As such, not a lot of data is available for the URN of unidentified vessels of opportunity (VOO), especially for small vessels that do not carry an automatic identification systems (AIS). To this end, we assembled a database of 1148 VOO’s URN from acoustic and visual recordings of ferries, fishing boats, yachts, and small speed boats made within Šibenik canal, Croatia. The database comprises source pressure levels at the closest point of approach, picture and video of the vessel, and the vessel’s speed, size, and type. A shared webpage allows filtering and comparing vessel types and characteristics. In this paper, we share the structure of our database, the analysis methodology. We conclude that the URN of small vessels is significant and compatible to large vessels.